Efficacy and safety of saxagliptin in older participants in the SAVOR-TIMI 53 trial - Leiter, Lawrence A; Teoh, Hwee; Braunwald, Eugene; Mosenzon, Ofri; Cahn, Avivit; Kumar, K M Prasanna; Smahelova, Alena; Hirshberg, Boaz; Stahre, Christina; Frederich, Robert; Bonnici, Francois; Scirica, Benjamin M; et al. (Diabetes care, 2015)
OBJECTIVE: To examine the safety and cardiovascular (CV) effects of saxagliptin in the predefined elderly (≥65 years) and very elderly (≥75 years) subpopulations of the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus-Thrombolysis in Myocardial Infarction 53 (SAVOR-TIMI 53) trial. RESEARCH DESIGN AND METHODS: Individuals ≥40 years (n = 16,492; elderly, n = 8,561; very elderly, n = 2,330) with HbA1c ≥6.5% (47.5 mmol/mol) and ≤12.0% (107.7 mmol/mol) were randomized (1:1) to saxagliptin (5 or 2.5 mg daily) or placebo in a double-blind trial for a median follow-up of 2.1 years. RESULTS: The hazard ratio (HR) for the comparison of saxagliptin versus placebo for the primary end point (composite of CV mortality, myocardial infarction, or ischemic stroke) was 0.92 for elderly patients vs. 1.15 for patients <65 years (P = 0.06) and 0.95 for very elderly patients. The HRs for the secondary composite end points in the entire cohort, elderly cohort, and very elderly cohort were similar. Although saxagliptin increased the risk of hospitalization for heart failure in the overall saxagliptin population, there was no age-based treatment interaction (P = 0.76 for elderly patients vs. those <65 years; P = 0.34 for very elderly patients vs. those <75 years). Among saxagliptin-treated individuals with baseline HbA1c ≥7.6% (59.6 mmol/mol), the mean change from baseline HbA1c at 2 years was -0.69%, -0.64%, -0.66%, and -0.66% for those ≥65, <65, ≥75, and <75 years old, respectively. The incidence of overall adverse events (AEs) and serious AEs was similar between saxagliptin and placebo in all cohorts; however, hypoglycemic events were higher for saxagliptin versus placebo regardless of age. CONCLUSIONS: The SAVOR-TIMI 53 trial supports the overall CV safety of saxagliptin in a robust number of elderly and very elderly participants, although the risk of heart failure hospitalization was increased irrespective of age category. AEs and serious AEs as well as glycemic efficacy of saxagliptin in elderly patients are similar to those found in younger patients.
Keywords: výsledek terapie; adamantan; Dipeptidyl-Peptidase IV Inhibitors; Male; srdeční selhání; glykovaný hemoglobin; Dipeptides; Adamantane; Drug Administration Schedule; Diabetic Angiopathies; hospitalizace; krevní glukóza; cévní mozková příhoda; vztah mezi dávkou a účinkem léčiva; Adult; Stroke; Aged; dospělí; Diabetes Mellitus, Type 2; mužské pohlaví; senioři; incidence; diabetes mellitus 2. typu; inhibitory dipeptidylpeptidasy 4; diabetické angiopatie; infarkt myokardu; dvojitá slepá metoda; Treatment Outcome; senioři nad 80 let; lidé; ženské pohlaví; Glycated Hemoglobin; Heart Failure; Humans; Hospitalization; Myocardial Infarction; Aged, 80 and over; dipeptidy; rozvrh dávkování léků; Double-Blind Method; Female; Blood Glucose; Dose-Response Relationship, Drug; lidé středního věku; Incidence; Middle Aged